From “Seeing Through” to “Seeing With”: Assessment Criteria and the Myths of Transparency - Bearman, Margaret; Ajjawi, Rola (Frontiers in Education, 2018)
The notion of ‘transparency’ has been extensively critiqued with respect to higher education. These critiques have serious implications for how educators may think about, develop and work with assessment criteria. This conceptual paper draws from constructivist and post-structural critiques of transparency to challenge two myths associated with assessment criteria: 1) transparency is achievable and 2) transparency is neutral. Transparency is interrogated as a social and political notion, which can never be attained but can be drawn from to fulfil various agendas. Some of these agendas support learning but this is not inevitable. This conceptual paper prompts educators and administrators to be mindful about how they think about, use and develop assessment criteria, in order to avoid taken-for-granted practices, which may not benefit student learning.